AXL confers intrinsic resistance to osimertinib and advances the emergence of tolerant cells - Hirokazu Taniguchi; Tadaaki Yamada; Rong Wang; Keiko Tanimura; Yuta Adachi; Akihiro Nishiyama; Azusa Tanimoto; Shinji Takeuchi; Luiz H. Araujo; Mariana Boroni; Akihiro Yoshimura; Shinsuke Shiotsu; et al. (2019)
A novel EGFR-tyrosine kinase inhibitor (TKI), osimertinib, has marked efficacy in patients with EGFR-mutated lung cancer. However, some patients show intrinsic resistance and an insufficient response to osimertinib. This study showed that osimertinib stimulated AXL by inhibiting a negative feedback loop. Activated AXL was associated with EGFR and HER3 in maintaining cell survival and inducing the emergence of cells tolerant to osimertinib. AXL inhibition reduced the viability of EGFR-mutated lung cancer cells overexpressing AXL that were exposed to osimertinib. The addition of an AXL inhibitor during either the initial or tolerant phases reduced tumor size and delayed tumor re-growth compared to osimertinib alone. AXL was highly expressed in clinical specimens of EGFR-mutated lung cancers and its high expression was associated with a low response rate to EGFR-TKI. These results indicated pivotal roles for AXL and its inhibition in the intrinsic resistance to osimertinib and the emergence of osimertinib-tolerant cells.